Clinical and Genetic Investigation of a Multi-generational Chinese Family Afflicted with Von Hippel-Lindau Disease - Jingyao Zhang; Jie Ma; Xiaoyun Du; Dapeng Wu; Hong Ai; Jigang Bai; Shunbin Dong; Qinling Yang; Kai Qu; Yi Lyu; Robert K Valenzuela; Chang Liu (Chinese Medical Journal, 2015)
Background: Von Hippel-Lindau (VHL) disease is a hereditary tumor disorder caused by mutations or deletions of the VHL gene. Few studies have documented the clinical phenotype and genetic basis of the occurrence of VHL disease in China. This study armed to present clinical and genetic analyses of VHL within a five-generation VHL family from Northwestern China, and summarize the VHL mutations and clinical characteristics of Chinese families with VHL according to previous studies. Methods: An epidemiological investigation of family members was done to collect the general information. A retrospective study of clinical VHL cases was launched to collect the relative clinical data. Genetic linkage and haplotype analysis were used to make sure the linkage of VHL to disease in this family. The VHL gene screening was performed by directly analyzing DNA sequence output. At last, we summarized the VHL gene mutation in China by the literature review. Results: A five-generation North-western Chinese family afflicted with VHL disease was traced in this research. The family consisted of 38 living family members, of whom nine were affected. The individuals afflicted with VHL exhibited multi-organ tumors that included pheochromocytomas (8), central nervous system hemangioblastomas (3), pancreatic endocrine tumors (2), pancreatic cysts (3), renal cysts (4), and paragangliomas (2). A linkage analysis resulted in a high maximal LOD score of 8.26 (theta = 0.0) for the marker D3S1263, which is in the same chromosome region as VHL. Sequence analysis resulted in the identiﬁcation of a functional C>T transition mutation (c. 499 C>T, p.R167W) located in exon 3 of the 167 th codon of VHL. All affected individuals shared this mutation, whereas the unaffected family members and an additional 100 unrelated healthy individuals did not. To date, 49 mutations have been associated with this disease in Chinese populations. The most frequent VHL mutations in China are p.S65 W, p.N78 S, p.R161Q and p.R167 W. Conclusions: The results supported the notion that the genomic sequence that corresponds to the 167 th residue of VHL is a mutational hotspot. Further research is needed to clarify the molecular role of VHL in the development of organ-specific tumors.